Kontribusi Teknologi Informasi dan Komunikasi terhadap Kelompok Ketimpangan Pendapatan Daerah - Dewi, Dyah Makutaning; Setiadi, Yaya; Ikhwanuddin, Mohammad; Fadhilah, Laila Amalia (UI Scholars Hub, 2022)
Inequality is one of the recent problems in Indonesia. Difference in Gini ratio in some provinces in the country is due to many factors, one of which is ICT. This study is analyze effect of ICT on Gini ratio in high and low inequality area in 2012–2018. Panel data regression is used as the analysis method. Results showed that in areas with high inequality, percentage of households that own or able to use computers had a positive and significant effect while the percentage of households accessing internet had a negative and significant effect on Gini ratio and in the areas with low inequality, the percentage of households accessing internet had a negative and significant effect on Gini ratio.